Effect of probiotic supplement (kidilact) on prevention of acute diarrhea in children: a double-blind randomized clinical trial - Hesaraki, Mehran (International Journal of Research in Medical Sciences, 2017)
Background: Acute viral diarrhea is one of the most common diseases in children, which is associated with high risk of mortality. The present study aimed to determine the effect of Kidilact on the treatment of children with acute diarrhea. Methods: This double-blind randomized clinical trial was conducted on 84 children aged 6-60 months with diarrhea, hospitalized in pediatric ward of Amir al-Mu'minin hospital of Zabol, Iran. The patients who met the inclusion criteria were included and assigned to the control and treatment groups (42 patients in each group). Data collection instruments included clinical examination of participants in terms of gender, medication, diet, stool test, weight, average heart rate, average respiratory rate, average body temperature, and average frequency of defecation Data was analyzed with descriptive and analytical tests (chi-square, Fisher's exact test, t-test, etc.) in SPSS-21. Results: Body temperature, heart rate, and frequency of defecation significantly reduced in the intervention group after three days (p<0.05). In addition, weight gain presented an improving trend in the intervention group, but not significantly different from the control group (p<0.05). Conclusions: Findings indicated that the use of Kidilact may be helpful in the treatment of acute viral diarrhea in children and play a key role in early recovery, reduction of disease severity, and improvement of vital signs in these patients.